CHYDENANTHUS MIERS (LECYTHIDACEAE): A CORRECTION - Kuswata Kartawinata (BRIN Publishing (Penerbit BRIN), 1984)
In my article on the genus ChydenmUhus Miers in Reinwardtia 10 (1) : 28, 1982, I stated that